Faith and Culture: Reconciling the Christian Belief with Igbo Faith Experience Today - Ezimakor, Jude, Lic. theol. (Tectum Verlag, 2021)
How do faith and culture interact? Using the example of the Igbo tribe in Nigeria, Jude Ezimakor explains their interplay and shows how the Christian faith can connect with human culture to give an authentic testimony of faith in concrete everyday experience.In particular, he explores the question of who Jesus Christ is for a particular community of believers and what meaning he can convey in their contemporary lives and their particular cultural life situations. In this way, Christology begins to merge Orthodoxy and Orthopraxis with the question: How does faith come alive in a particular social-cultural context in order to develop it?